2010
DOI: 10.1063/1.3478556
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional hole gas induced by polarization in (0001)-oriented metal-face III-nitride structure

Abstract: Polarization-doping via graded AlGaN layer on N-face (0001¯) GaN has been demonstrated as an inspiring p-type doping method for wide-band-gap nitrides. However, the polarity of III-nitrides grown by metal organic chemical vapor deposition is metal-face typically. In this paper, we show that three-dimensional mobile hole gas induced by polarization can be formed in (0001)-oriented metal-face III-nitride structure. The hole concentration of a Mg-doped AlxGa1−xN layer with graded Al composition from x=0.3 to 0 gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
59
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 7 publications
1
59
0
1
Order By: Relevance
“…Both N-face [9,28,29,32] and the conventional metal-face [30,31,33] growth can benefit from compositional grading, producing a flat and smooth valence band profile right up to the edge of the active region to ensure superlative hole injection efficiency. If N-face growth is adopted, one must not only ensure good crystalline quality of the epitaxial layers, but also make Ohmic contact to a wide bandgap p-type layer [31].…”
Section: Algan Based Duv Laser Diode Using Inverse-tapered P-waveguidementioning
confidence: 99%
See 1 more Smart Citation
“…Both N-face [9,28,29,32] and the conventional metal-face [30,31,33] growth can benefit from compositional grading, producing a flat and smooth valence band profile right up to the edge of the active region to ensure superlative hole injection efficiency. If N-face growth is adopted, one must not only ensure good crystalline quality of the epitaxial layers, but also make Ohmic contact to a wide bandgap p-type layer [31].…”
Section: Algan Based Duv Laser Diode Using Inverse-tapered P-waveguidementioning
confidence: 99%
“…Several articles are cited in Satter et al [3] which report new strategies for reduction of the high activation energy of Mg dopants or the increase of free hole concentration in III-N materials. A technique known as "polarization doping" has been suggested for the improvement of p-type dopant (Mg) ionization efficiency in compositionally graded AlGaN layers through the field ionization of the dopant atoms via the electric field induced by polarization charge [9,[28][29][30][31][32][33]. This appellation is somewhat misleading, as electric fields of sufficient magnitude to ionize deep acceptor atoms would necessarily drive free carriers away from the high-field region, leaving behind only fixed space charge rather than highly conductive material.…”
Section: Algan Based Duv Laser Diode Using Inverse-tapered P-waveguidementioning
confidence: 99%
“…To improve internal quantum efficiency, grading has been used in InGaN/AlInGaN quantum wells (QW) based LEDs [10,11,12] with reported 5-6 times enhancement in radiative recombination. Currently, grading schemes have improved carrier injection [10,13,14], and doping [15] in UV-LEDs emitting around 280nm. To date, UV LEDs were championed by SETI Corporation with record external efficiency of more than 11% at 278nm emission wavelength [16].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 To this end, tremendous efforts have been devoted to improve the LED performance through addressing various issues related to material quality, structure optimization, and device design and fabrication. [3][4][5][6][7][8][9][10][11][12] Among these issues, to date a low p-type doping efficiency remains as a limiting factor, which adversely affects the LED performance. In typical p-type GaN, the resulting hole concentration is low because only $1% of Mg dopants are ionized at room temperature.…”
mentioning
confidence: 99%
“…9 Recently, it has been also reported that the hole concentration can be increased through the polarization doping. 10,11 The GaN/Al x Ga 1Àx N heterostructures grown along the polar orientations exhibit strong spontaneous and piezo-electric polarizations. 13 Such strong polarizations can induce electric fields causing significant band bending in the GaN/Al x Ga 1Àx N heterostructures.…”
mentioning
confidence: 99%